Shivasia gen. nov. for the Australasian smut Ustilago solida that historically shifted through five different genera - Matthias Lutz; Kálmán Vánky; Marcin Piątek (IMA Fungus)
The generic position of the enigmatic smut fungus Ustilago solida is evaluated applying molecular phylogenetic analyses using ITS and LSU rDNA sequences as well as light and scanning electron microscopical investigations of several collections of this species. Ustilago solida has previously been included in five different genera (Ustilago, Urocystis, Sorosporium, Cintractia, and Tolyposporium), however, molecular analyses revealed that this smut does not belong to any of these genera and represents a distinct ustilaginalean lineage. The closest known phylogenetic relative of Ustilago solida is Heterotolyposporium lepidospermatis, the type species of the monotypic genus Heterotolyposporium. Both smuts differ considerably in both LSU sequences and in several morphological traits, such as the structure of sori and the characteristics of spore balls. Accordingly, the new genus Shivasia is described to accommodate Ustilago solida. This smut infects different Schoenus species (Cyperaceae) in Australia and New Zealand. The description of Shivasia increases the number of endemic smut genera in Australasia to ten. Compared to all other continents the number of endemic smut genera is exceptionally high, which may point at fast evolving characters and/or may be caused by the regional history, including the long-term geographic isolation of Australasia.